DETERMINATION OF THE TYPES OF PUBLIC SERVICE IN TERMS OF THE RULES OF LEGISLATIVE TECHNIQUE - Ковалева, Юлия; Серашов, Владимир (Modern engineering and innovative technologies, 2017)
The paper deals with the problem of classification of types of civil service with regard to the appearance in the basic law governing the civil service in the Russian Federation of the term “public service of other types”. The specified term in relation t